2008
DOI: 10.4049/jimmunol.180.3.1818
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine 1-Phosphate 1 and TLR4 Mediate IFN-β Expression in Human Gingival Epithelial Cells

Abstract: IFN-β production is a critical step in human innate immune responses and is primarily controlled at the transcription level by highly ordered mechanisms. IFN-β can be induced by pattern-recognition receptors such as the TLR4. S1P1 is a G protein-coupled receptor, which has a high affinity for sphingosine 1-phosphate (S1P). Although many of the receptors and signaling pathways leading to the expression of IFN-β have been identified and characterized, it is still unclear how IFN-β is regulated in primary human g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
2
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 35 publications
2
15
2
1
Order By: Relevance
“…TLR4 activates PI3K to maximize IRF3 activation and subsequently induce IFN-b and IP-10 in human epithelial cells (36). In our study, we found that Gab1 enhances TLR3-and TLR4-triggered activation of MAPKs, NF-kB, but also promotes MyD88-dependent, TRIF-dependent, or RIG-Itriggered IRF3 activation.…”
Section: Discussionsupporting
confidence: 53%
“…TLR4 activates PI3K to maximize IRF3 activation and subsequently induce IFN-b and IP-10 in human epithelial cells (36). In our study, we found that Gab1 enhances TLR3-and TLR4-triggered activation of MAPKs, NF-kB, but also promotes MyD88-dependent, TRIF-dependent, or RIG-Itriggered IRF3 activation.…”
Section: Discussionsupporting
confidence: 53%
“…In macrophages and T cells, S1P attenuates TLR2 signaling and TLRinduced IL-8 production, respectively [39,40]. In contrast, S1P and TLR4 cooperatively induce pro-inflammatory cytokine expression and type I IFNs in gingival epithelial and endothelial cells [28,29,41]. We show here that IL-6 and IL-8 production is increased by costimulation with S1P and Pam 3 CSK 4 or poly(I:C) (Fig.…”
Section: Discussioncontrasting
confidence: 55%
“…Plots of GPLSs from the 32 genes in cluster 219, 220, and 243 showed very similar patterns, all having a major peak at one end of chromosome 13, a secondary peak on chromosome 10, and a third peak on chromosome 4 (Figure 3A–3E). Among the 32 genes in the three clusters, at least 16 (50%; Oas1g, Tgfb3, Tnfrsf12a, Stat2, Parp14, Oas1a, Adar1, Mx2, Irf7, S1pr5, Oas2, Dhx58, Ifit3, Usp18, Isg15, and Ifi35 ) were known to play a role (or induced by) in the IFN-I response (Chapman et al, 2013; Eskan et al, 2008; George et al, 2011). Search of an interferon database (Rusinova et al, 2013) identified an additional nine genes ( Hbegf, Cstb, Fcγr1, Tnc, Errfi1, Wisp1, Kazad1, Rtp4, and B430306N03Rik ) that have been implicated in the IFN-I response, increasing the percentage to 78.1% (25/32).…”
Section: Resultsmentioning
confidence: 99%